Adaptive radiation at a low taxonomic level: Divergence in buoyancy of the ecologically similar Antarctic fish Notothenia coriiceps and N. rossii - Eastman, Joseph T. (2011)
We studied the buoyancy of 263 specimens of the sympatric sister species Notothenia coriiceps and N. rossii captured at King George Island. In these species without a swim bladder, we expressed measurements of buoyancy as percentage buoyancy (%B = weight in water/weight in air × 100), with smaller numbers reflecting more buoyant (i.e. less dense) species. Mean %B of N. coriiceps (4.34%) was significantly greater than that of N. rossii (3.82%), reflecting the lower density and more active swimming, migratory, and feeding behavior of N. rossii compared to N. coriiceps. Skeletal weight as a percentage of body weight was also significantly greater in N. coriiceps (2.46%) than N. rossii (1.65%). Paradoxically, the weight of the vertebral column as a percentage of skeletal weight was significantly greater in N. rossii (28.01%) than in N. coriiceps (24.29%); however, this is intelligible in light of the bone anatomy and histology. Our sample encompassed a wide size and age range, and trend lines for scatter plots of %B against standard length were curvilinear for both species, peaking at 140 to 160 mm, a phenomenon not previously seen in studies of notothenioid buoyancy. We conclude that the ontogenetic increase in %B (reduced buoyancy) in fingerlings/young juveniles and the ontogenetic decrease in %B (increased buoyancy) in older juveniles/immature adults reflects disproportionate growth of skeletal and visceral tissues, respectively, and is not causally related to concurrent pelagic-demersal habitat shifts.